New-Onset Atrial Fibrillation and Adverse In-Hospital Outcome in Patients with Acute Pulmonary Embolism - Tang, Ri-Bo; Jing, Yan-Yan; Xu, Zhi-Yuan; Dong, Jian-Zeng; Du, Xin; Wu, Jia-Hui; Yu, Rong-Hui; Long, De-Yong; Ning, Man; Sang, Cai-Hua; Jiang, Chen-Xi; Bai, Rong; Liu, Nian; Wen, Song-Nan; Li, Song-Nan; Chen, Xuan; Huang, Shu-Tao; Cui, Yi-Kai; Ma, Chang-Sheng (Seminars in Thrombosis and Hemostasis, 2020)
Atrial fibrillation (AF) can be secondary to acute pulmonary embolism (PE). This study aimed to investigate the prognostic impact of new-onset AF on patients with acute PE. In this study, 4,288 consecutive patients who were diagnosed with acute PE were retrospectively screened. In total, 77 patients with acute PE and new-onset AF were analyzed. Another 154 acute PE patients without AF were selected as the age- and sex-matched control group. Adverse in-hospital outcome comprised one of the following conditions: all-cause death, endotracheal intubation, cardiopulmonary resuscitation, and intravenous catecholamine therapy. The patients with new-onset AF had higher prevalence of congestive heart failure, higher simplified PE severity index (sPESI), higher creatinine, and larger left atrium diameter. The incidences of adverse in-hospital outcomes were 10.4 and 2.6% in patients with new-onset AF and no AF, respectively (p = 0.02). Patients with sPESI ≥ 1 had higher incidence of adverse in-hospital outcomes than those with sPESI = 0 (9.4 vs. 0.9%, p < 0.01). The area under the receiver operating characteristic curve of sPESI and sPESI + AF (adding 1 point for new-onset AF) scores in assessing the adverse in-hospital outcome were 0.80 (95% confidence interval [CI]: 0.68–0.93) and 0.84 (95% CI: 0.72–0.96), respectively. In multivariable analysis, sPESI ≥ 1 (odds ratio, 8.88; 95% CI: 1.10–72.07; p = 0.04) was an independent predictor of adverse in-hospital outcome. However, new-onset AF was not an independent predictor. In the population studied, sPESI is an independent predictor of adverse in-hospital outcomes, whereas new-onset AF following acute PE is not, but it may add predictive value to sPESI.
Keywords: pulmonary embolism; PE; atrial fibrillation; AF; prognosis